2008
DOI: 10.1097/bpo.0b013e3181653b6f
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaneurysm After Ponseti Percutaneous Achilles Tenotomy

Abstract: The Ponseti method has become a popular technique to treat idiopathic clubfoot. In most cases, a percutaneous Achilles tenotomy is required to correct residual equinus contracture. Bleeding has been reported as a complication of percutaneous tenotomy. We present a case of a baby who developed a pseudoaneurysm after undergoing an appropriate Ponseti percutaneous Achilles tenotomy at the age of 8 weeks. The diagnosis of pseudoaneurysm was confirmed by color ultrasonography, which showed active flow in the base o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 23 publications
0
49
0
1
Order By: Relevance
“…For this purpose, blade modifications and different techniques of tenotomy were introduced in order to avoid any neurovascular injury [5,7]. Some authors recommended a small open incision to directly visualise the tendon before severing it to decrease the risk of neurovascular injury, but the results and the details of the technique are lacking [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, blade modifications and different techniques of tenotomy were introduced in order to avoid any neurovascular injury [5,7]. Some authors recommended a small open incision to directly visualise the tendon before severing it to decrease the risk of neurovascular injury, but the results and the details of the technique are lacking [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Although percutaneous Achilles tenotomy is a relatively simple technique with low complication rates, articles reporting complications increases as the technique becomes more popular [5,6]. Recently, different tenotomy techniques and new designs of surgical blade modifications have taken place in the literature, in order to perform the technique in a safer fashion [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…71,[75][76][77][78] In these cases, the blood supply occurs separately through the fibular artery. 73 …”
Section: Pathological Anatomymentioning
confidence: 99%
“…These include excessive bleeding, attributed to lesion of the posterior fibular artery or saphenous vein 118 and formation of pseudoaneurysm. 73 Clinical studies with late follow-up showed that tenotomy does not cause late onset effects such as tendon weakening and ruptures. 53,60,113,120,121 Previous studies on other types of disease showed that there is complete repair of the calcaneal tendon after its total sectioning at the myotendineous junction 122 , or more distally.…”
Section: Calcaneal Tendon Sectioningmentioning
confidence: 99%
See 1 more Smart Citation